MANAJEMEN FUNDRAISING LSM DALAM MENDUKUNG PENDANAAN DAN KEBERLANJUTAN ORGANISASI (Study Kasus Pada LSM Marifad Banda Aceh) - Surna Lastri (Jurnal Akuntansi Muhammadiyah (JAM), 2013)
NGOs have different characteristics compared to business organizations, the main and fundamental difference lies in the way NGOs obtain funding needed to carry out various activities. In connection with raising funds to finance the program and activities of the NGO operations, fundraising is discussion among NGOs. But the evidence indicates that most of the NGOs now have not been up to doing fundraising so the impact on the lack of availability of fund. Purpose this study was to obtain an overview of the management of NGO fundraising in support of funding and sustainability of the organization through planning, implementing fundraising strategies and managing funds to NGOs Marifad in Banda Aceh. This study was conducted with a qualitative approach where data were obtained through in-depth interviews and gathering materials related material as well as direct observation at Marifad NGOs in Banda Aceh.The results showed that fundraising activities are the backbone of the organization in exploring funding. Fundraising strategy within an organization is an analysis tool to identify potential funding sources to make sustainability and existence lembaga.LSM Marifad have built systems management agency reserve funds provided for in the financial SOP. SOP financial load on system and standard financial procedures, the goal is to build financial management mechanisms that are transparent and accountable, this is all done in an effort to increase the trust to those donors that have an impact on increasing fundraising organization.Â Keywords: Fundraising, Funding, Sustainability, NGO.